THE EFFECT OF BOARD SIZE AND BOARD INDEPENDENCE TOWARD THE EARNINGS MANAGEMENT PRACTICE AT THE PROPERTY AND REAL ESTATE COMPANY LISTED IN INDONESIA STOCK EXCHANGE - admin, Farah Juniati Meutianingrum B42112010 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Board of directors as the internal mechanism of good corporate governance play a vital role in controlling agency problem between shareholders and managers arise due to earnings management. This research investigates the roles of board director size and independent members on the board director towards earnings management practices. This research is quantitative research that use secondary data downloaded from idx.co.id. Research?s sample is 25 property and real estate companies selected randomly, the period of observation is 3 years from 2012-2014. The proxy of earnings management is Discretionary Accruals which calculated using Modified Jones Model. Using Board size and board independence as the independent variable, the finding is earnings management partially has positive and not significantly related to the board size and board independence. Also, the investigation of the simultaneous effect, the data shows that the board size and the percentage of independent board members are positive but not significantly related to earnings management.   Keywords: earnings management, discretionary accruals, good corporate governance, board size, board independence.